2018
DOI: 10.1177/2473011418780437
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ankle Arthrodesis vs ORIF for Severely Comminuted Pilon Fractures

Abstract: Background: The treatment for highly comminuted pilon fractures remains controversial. The goal of this retrospective cohort study was to compare functional outcomes of primary arthrodesis of the tibiotalar joint (fusion) and open reduction internal fixation (ORIF). Methods: Patients who underwent primary ORIF or fusion for pilon fractures at our institution since 2000 were identified by Current Procedural Terminology (CPT) code. Inclusion criteria for the ORIF cohort were patients with an AO/Orthopaedic Traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…In these articles, the outcomes were reported as the total number of the complication of interest for 1 treatment group compared with another treatment group, but without distinction as to whether the complication occurred in AO 43-C1 or AO 43-C3 injury or the status of the skin at the time of injury. The remaining 13, with 8 articles reporting a staged approach [3,15,[24][25][26][27][28][29] and 5 articles pertaining to primary arthrodesis [8,[20][21][22][23] were evaluated and analyzed. The 13 studies examined in this review included 377 total fractures, 228 of which involved AO 43-C3 pilon fractures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these articles, the outcomes were reported as the total number of the complication of interest for 1 treatment group compared with another treatment group, but without distinction as to whether the complication occurred in AO 43-C1 or AO 43-C3 injury or the status of the skin at the time of injury. The remaining 13, with 8 articles reporting a staged approach [3,15,[24][25][26][27][28][29] and 5 articles pertaining to primary arthrodesis [8,[20][21][22][23] were evaluated and analyzed. The 13 studies examined in this review included 377 total fractures, 228 of which involved AO 43-C3 pilon fractures.…”
Section: Resultsmentioning
confidence: 99%
“…None of the 13 studies examined all the assessed variables in this review. Only one of the studies was a comparative study [23], the rest were case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PICO Question 1: Short-Term Complications Using primary arthrodesis for severely comminuted pilon fractures is not a novel concept. Beckwitt et al examined the differences in patient outcomes between primary arthrodesis and primary ORIF in AO-43C3 pilon fractures and found that patients treated with the arthrodesis approach had a lower rate of nonunion (23). While this study was notable in that the average follow-up was 73.7 months, like the other studies included in this review, it did not have a treatment arm involving staged treatment (primary ORIF was the comparator group).…”
Section: Discussionmentioning
confidence: 97%
“…Arthrodesis: Some studies consider primary arthrodesis for severely comminuted pilon fractures. Beckwitt et al [66] reports a lower rate of nonunion and similar functional outcomes to ORIF in a relatively young cohort of patients with these injuries. They continue to conclude that performing primary arthrodesis in severely comminuted pilon fractures reduces the need for further operations.…”
Section: Intramedullary Nail (Imn)mentioning
confidence: 88%